Feminist ecological economics. - Perkins, Ellie; Kuiper, Edith; Quiroga-Martínez, Rayén; Turner, Terisa E.; Brownhill, Leigh S.; Mellor, Mary; Todorova, Zdravka; Jochimsen, MarenA.; McMahon, Martha (Feminist Economics, 2005)
These Explorations argue that more links between the fields of feminist ecology and feminist economics are both needed and promising, and presents new, boundary-crossing research in this area. It brings together contributions from various regions in the world that link political action and experience in practice and research in an economic theorizing that includes both environmental and feminist concerns.